2022
DOI: 10.6004/jnccn.2022.7052
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Frailty and Time Alive and At Home After Cancer Surgery Among Older Adults: A Population-Based Analysis

Abstract: Background: Although frailty is known to impact short-term postoperative outcomes, its long-term impact is unknown. This study examined the association between frailty and remaining alive and at home after cancer surgery among older adults. Methods: Adults aged ≥70 years undergoing cancer resection were included in this population-based retrospective cohort study using linked administrative datasets in Ontario, Canada. The probability of remaining alive and at home in the 5 years after cancer resection was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The results of this study cannot be used in isolation and should be combined with all the data available to clinicians when discussing transfer to ICU and implementation of aggressive life-prolonging measures. Indeed, one in five older adults admitted to the ICU after cancer surgery will die in hospital with key patient groups, such as those with baseline frailty being at higher risk for poor outcomes [ 8 , 62 ]. However, the ability to accurately determine which patients will survive their hospitalization at the time of ICU admission remains challenging and there may be discrepancies in perceived outcomes between the surgical and ICU teams, patients, and families [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study cannot be used in isolation and should be combined with all the data available to clinicians when discussing transfer to ICU and implementation of aggressive life-prolonging measures. Indeed, one in five older adults admitted to the ICU after cancer surgery will die in hospital with key patient groups, such as those with baseline frailty being at higher risk for poor outcomes [ 8 , 62 ]. However, the ability to accurately determine which patients will survive their hospitalization at the time of ICU admission remains challenging and there may be discrepancies in perceived outcomes between the surgical and ICU teams, patients, and families [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Hallet et al 5 clearly showed the importance of considering frailty as an important factor in evaluating older adults before oncologic surgery. However, we need to keep in mind that the surgery itself may not contribute as much as frailty to the long-term outcomes.…”
Section: See Page 1223 For Related Articlementioning
confidence: 99%
“…The study by Hallet et al 5 has the potential of stimulating further studies that could prospectively evaluate this important long-term outcome with a more thorough geriatric assessment before oncologic surgery and more detailed capture of functional outcomes after surgery. For example, in a prospective study published in 2020 that involved 229 patients before an elective surgery for solid tumors, of those alive at 1 year, 26% were institutionalized, and by 2 years, almost half of the entire cohort (46%) were institutionalized or had died.…”
Section: See Page 1223 For Related Articlementioning
confidence: 99%
See 2 more Smart Citations